Gastroprotective Activities of Ethanol Extract of Black Rice Bran (Oryza sativa L.) in Rats - Peerachit Tonchaiyaphum; Warangkana Arpornchayanon; Parirat Khonsung; Natthakarn Chiranthanut; Pornsiri Pitchakarn; Puongtip Kunanusorn (Molecules, 2021)
Black rice is a type of rice in the Oryza sativa L. species. There are numerous reports regarding the pharmacological actions of black rice bran, but scientific evidence on its gastroprotection is limited. This study aimed to evaluate the gastroprotective activities of black rice bran ethanol extract (BRB) from the Thai black rice variety Hom Nil (O. sativa L. indica) as well as its mechanisms of action, acute oral toxicity in rats, and phytochemical screening. Rat models of gastric ulcers induced by acidified ethanol, indomethacin, and restraint water immersion stress were used. After pretreatment with 200, 400, and 800 mg/kg of BRB in test groups, BRB at 800 mg/kg significantly inhibited the formation of gastric ulcers in all gastric ulcer models, and this inhibition seemed to be dose dependent in an indomethacin-induced gastric ulcer model. BRB could not normalize the amount of gastric wall mucus, reduce gastric volume and total acidity, or increase gastric pH. Although BRB could not increase NO levels in gastric tissue, the tissue MDA levels could be normalized with DPPH radical scavenging activity. These results confirm the gastroprotective activities of BRB with a possible mechanism of action via antioxidant activity. The major phytochemical components of BRB comprise carotenoid derivatives with the presence of phenolic compounds. These components may be responsible for the gastroprotective activities of BRB. The 2000 mg/kg dose of oral BRB showed no acute toxicity in rats and confirmed, in part, the safe uses of BRB.